Exploring the drivers and the interventions towards sustainable food security in the food supply chain - Chan, Hao Yuan; Abdul Halim-Lim, Sarina; Tan, Tai Boon; Kamarulzaman, Nitty Hirawaty; Jamaludin, Adi Ainurzaman; Wan-Mohtar, Wan Abd Al Qadr Imad (Multidisciplinary Digital Publishing Institute, 2020)
The sustainability of food security is a global concern, and one of the priorities related to it is the ability to identify effective efforts that can protect food security along the food supply chain (FSC). The present study demystifies the relation of sustainability and food security and structurally identifies the sustainable drivers, and the pragmatic interventions that can critically contribute to the sustainability of food security within each stage of the FSC. A systematic review of articles from six databases was implemented. Thematic analysis was engaged to detect the sustainable drivers and interventions practised at each stage in the FSC for food security purposes. Six main themes of the drivers and interventions were derived from the analysis: food security governance involvement, input resource management, output management, information sharing, income, and technology. The result identifies the potential that quality management has on the mediating effect towards sustainable food security, through which a conceptual model for sustainable food security in the FSC was thus developed. It is deduced that mapping and categorizing the drivers and intervention of sustainable food securities could help deepen the understanding of effective and innovative practices towards food security in the FSC.